Gender and education In África: the case choice of the choice of baccalaureate studies in Ecuatoguinean educational centers - Obiang-Mikue , Bonifacio Nguema (2024)
This research focuses on the gender and education approach in Africa, as one of the main scenarios where the difficulties of access to education are registered, prioritizing more the training of boys to the detriment of girls. In order to better understand this issue, the analysis is focused on the specific case of the choice of high school studies in Equatoguinean schools. There is evidence of a division of the student body when it comes to choosing the branches of the baccalaureate, with students opting for the science or technology branch, while female students opt for the arts or humanities. As for the methodological aspects, the use of descriptive research based on the quantitative method was deemed necessary. This was chosen because the object of study is expressed in percentages. The population studied is Equatorial Guinea with a representative sample made up of educational centers under study, such as the Colegio Privado Nuestra Señora de Bisila de Nkolombong; Centro Educativo Madre Catalina II; Centro Privado la Divina Pastora; INES Carlos Lwanga; INES Padre Joaquín María Sialo, all in the city of Bata (mainland).  And the Nostradamus Private Center of the city of Malabo (insular part). One of the main conclusions is that girls opt more for the letters branch because hypothetically, this is related to feminine stereotypes, i.e. easy. Therefore, it is recommended to the students to show their cognitive skills regardless of sex.